TAOK3, a novel genome-wide association study locus associated with morphine requirement and postoperative pain in a retrospective pediatric day surgery population - Cook-Sather, Scott D. (2014)
Candidate gene studies have revealed limited genetic bases for opioid analgesic response variability. Genome-wide association studies (GWAS) facilitate impartial queries of common genetic variants, allowing identification of novel genetic contributions to drug effect. Illumina single nucleotide polymorphism (SNP) arrays were used to investigate SNP associations with total morphine requirement as a quantitative trait locus and with postoperative pain in a retrospective population of opioid-naïve children age 4 – 18 y who had undergone day surgery tonsillectomy and adenoidectomy. In an independent replication cohort, significant GWAS-identified SNPs were assayed using Taqman probes. Among 617 comprehensively phenotyped children, the 277 subjects of European Caucasian (EC) ancestry demonstrated nominal association between morphine dose and a series of novel SNPs (top rs795484, p=1.01×10(-6) and rs1277441, p=2.77×10(-6)) at the TAOK3 locus. Age, body mass index, and physical status were included covariates. Morphine requirement averaged 132.4 mcg/kg (SD 40.9). Each minor allele at rs795484 (G>A) contributed +17.6 mcg/kg (95% CI=10.7-24.4) to dose. Effect direction and magnitude were replicated in an independent cohort of 75 EC children (p<0.05). No association with morphine dose was detected in African Americans (AA) (n=241). Postoperative pain scores ≥ 7/10 were associated with rs795484 (G>A) in the EC cohort (OR=2.35, 95% CI=1.56-3.52, p<0.00005) and this association replicated in AA children (OR=1.76, 95% CI=1.14-2.71, p<0.01). Variants in TAOK3 encoding the serine/threonine-protein kinase, TAO3, are associated with increased morphine requirement in children of EC ancestry and with increased acute postoperative pain in both EC and AA subjects.